APLIKASI FORECASTING MENGENAI ANGKA KELAHIRAN DI KOTA KENDARI MENGGUNAKAN METODE REGRESI LINEAR BERGANDA (STUDI KASUS : DINAS KESEHATAN KOTA KENDARI) - Nike Syafitri; Sutardi Sutardi; LM Tajidun (semanTIK, 2018)
Birth rate is a very useful indicator not only of health status but also of overall population status, and the economic conditions in which the population lives. Population density in Kendari city in 2015 reached 1,174 people / km2. Population density in 10 sub-districts is quite diverse with the highest population density located in Kadia with the lowest density of 6,180 people / km2 in Baruga of 472 people/ km2. The purpose of this application is to predict the birth rate in Kendari by using multiple linear regression method.The Multiple Linear Regression Method is the most appropriate approach to predict future birth rates. An analysis that has more than one independent variable is called multiple linear regression analysis. The result of this system in the form of forecasting applications that can predict the birth rate in every month from all sub-districts in the  Kendari and provide information about how strong the relationship between the factors that affect the birth rate.Keywords— Forecasting, Birth Rate, Multiple Linear Regression, Correlation DOI : 10.5281/zenodo.1402398